Analisa Algoritma Naïve Bayes Classifier (NBC) Untuk Prediksi Penjualan Alat Kesehatan : Naïve Bayes Classifier (NBC) Algorithm Analysis for Prediction Medical Device Sales - Ramadhani, Dian; A’yuniyah, Qurotul; Elvira, Winda; Nazira, Nanda; Ambarani, Isnani; Intan, Sofia Fulvi (Institut Riset dan Publikasi Indonesia, 2023)
The application of Data Mining in the business scope can be found in the use of Customer Relationship Management (CRM). CRM is a company's effort to manage its sales and customers more optimally. Company Sales Data can be processed into knowledge that can be used to optimize marketing strategies. Purna Karya Scientific is a company engaged in the field of medical/medical devices, laboratory equipment, chemical and dental materials as well as educational aids. In this study has used sales data at PT. After Scientific Work with attributes item code, relation, number of items, and label as class. Then classify medical device sales data by implementing the Naïve Bayes Classifier (NBC) algorithm which can predict sales results by displaying an accuracy value. Implementation was carried out using Google Colab to obtain an accuracy value of 95%, a recall value of 95%, and a precision value of 81%. The results of data on sales of medical devices with 2 classes namely